Akutagawa Ryunosuke's Repertoire in the Short Story "Rashomon" - Aulia Rahman; Fakhria Nesa (IZUMI, 2023)
An author's creative process cannot be separated from the storehouse of knowledge obtained from different results of reading, hearing, or observing of the events around him. This store of knowledge, when juxtaposed with the concept introduced by Wolfgang Iser in his book The Act of Reading: A Theory of Aesthetic Response (1987), can be called a Repertoire. Shortly, repertoire can be understood as the basis for creating a work, as the background to make the foreground the author aims at through his work. This process also applies to Akutagawa Ryuunosuke's short story entitled Rashomon as the foreground of Konjakumonogatari, the 29th volume of the 18th story. This research aims to describe how the social, historical, and cultural writings by Akutagawa Ryunosuke in the Rashomon and compared with Konjakumonogatari, using the Aesthetic Repertoire theory proposed by Wolfgang Iser. The process through which, among others, grouping the data to be analyzed is related to social, historical, and cultural norms of Japanese society. Next, compare the data to see the relationship between Rashomon and Konjakumonogatari. The results showed (1) There are similarities between social, historical, and cultural similarities between literature and reality, (2) Social norms indicate the life of the Japanese lower class in the Heian period called Genin, (3) Historical norms show the dark conditions that Japanese people went through in the Heian era, because of the many problems that occurred at that time, and (4) Cultural Norms show the efforts made by Japanese people in the Heian period to survive despite hurting others. gb777gb777slot gacorgb777gb777GB777GB777slot gacorslot gacor